Analysis of the Influence of Corporate Maturity Mismatch on the Digital Transformation of Manufacturing Companies in Indonesia - Bunga Aulia Juhedi; Ulpah, Maria (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Digital transformation has become a strategic necessity for companies to maintain competitiveness amid industry disruption. However, the adoption of digital transformation does not always run smoothly because it is influenced by the gap between the structural readiness of the company and the need for long-term investment, known as corporate maturity mismatch. This study aims to analyze the impact of the level of corporate maturity mismatch on the implementation of digital transformation in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. The method used is a quantitative approach with panel data regression analysis, and digital transformation is measured based on the intensity of digital keyword usage in company annual reports. The results indicate that corporate maturity mismatch has a positive impact on overall digital transformation, as well as on fundamental technology categories such as Artificial Intelligence, Blockchain, Cloud Computing, and Big Data. Conversely, no significant impact was found on digital transformation in extended applications technology. These findings indicate that mismatches in financial structure drive companies to respond to such pressures through investments in strategic and long-term digital technologies. This study provides important implications for policymakers and industry players in designing funding strategies and regulations to support the acceleration of national digital transformation.